Effect of Working After Retirement on the Mental Health of Older People: Evidence From China - Xie, Lin; Yao, Yi-dan; Tang, Li-li; Zhang, Shuo; Yang, Hua-lei; Zhang, Si-qing; Wu, Yuan-yang; Li, Zhi-yun (Frontiers in Psychiatry, 2021)
There is little empirical research on the effect of working after retirement on the mental health of the older adults in China. To fill this gap in the literature, this study examines the effects of working after retirement on the mental health of the older adults using data from the China Family Panel Studies. We employed the methods of ordinary least squares, ordered logit, and propensity score matching–difference in differences (PSM–DID). Results show that working after retirement is negatively related to mental health of the older adults in China. The deterioration effect of post-retirement work mainly impacts those aged over 60 years, women, and those with lower education background, urban household registration, higher pension, and higher social status. Working after retirement is negatively related to mental health through the mediating effects of deteriorating interpersonal relationships and lower positive attitude. It is necessary to consider mental health effects and their population differences to evaluate the impact and improve the quality of policies of active aging.